Twenty Years of Multicultural Education Scholarship: Insights from the Journal for Multicultural Education and the Multicultural Education Technology Journal - Prahmana, Rully Charitas Indra; Ishartono, Naufal; Ahyan, Shahibul (Universitas Muhammadiyah Surakarta, 2026)
Despite the rapid growth of multicultural education research worldwide, systematic insights into how this field has evolved across major scholarly outlets over time remain limited. This study presents a literature review of twenty years of multicultural education scholarship published in two leading journals, the Multicultural Education Technology Journal and the Journal for Multicultural Education. Drawing on systematic content and narrative analysis of 521 Scopus-indexed articles, the review explores publication trends, author affiliations, thematic development, citation patterns, and keyword co-occurrence across two editorial phases. The findings reveal a clear shift from a technology-oriented focus (2007–2013) toward a broader and more interdisciplinary multicultural education agenda (2014–2025). Malaysia and the United States emerge as the most prolific contributors, while dominant research themes include inclusive education, teacher preparation, linguistic diversity, and culturally responsive pedagogy. Citation patterns suggest growing scholarly influence, including among early-career publications, alongside increasing international and interdisciplinary collaboration. Although the analysis is limited to Scopus-indexed sources, the findings provide valuable insights for scholars, editors, and policymakers seeking to strengthen equity-oriented educational research. Overall, this review contributes institutional knowledge on the evolution, internationalization, and educational impact of multicultural education research over the past two decades.